1988
DOI: 10.1002/art.1780310614
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐6 in synovial fluid and serum of patients with rheumatoid arthritis and other inflammatory arthritides

Abstract: Interleukin-6 (IL-6), also called 26-kd protein, hybridoma plasmacytoma growth factor, beta 2-interferon, or B cell stimulatory factor 2, is a recently described human cytokine with multiple growth and differentiation activities. Using a very sensitive bioassay based on the growth factor activity of this protein for B cell hybridomas, we found that IL-6 activity was significantly elevated in synovial fluid from patients with rheumatoid arthritis (RA) or other inflammatory arthritides, as compared with that in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
342
1
15

Year Published

1993
1993
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 798 publications
(379 citation statements)
references
References 16 publications
21
342
1
15
Order By: Relevance
“…OA FLS also express BAFF on their membrane and release minute amounts of IL-6 (ref. 32 and Figure 6C in the present study). As a consequence, B cells may expand clonally and hypermutate somatically in the presence of OA FLS (41).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…OA FLS also express BAFF on their membrane and release minute amounts of IL-6 (ref. 32 and Figure 6C in the present study). As a consequence, B cells may expand clonally and hypermutate somatically in the presence of OA FLS (41).…”
Section: Discussionsupporting
confidence: 76%
“…Among these observations are our previous studies showing that IL-6 contributes to the expression of RAG in mature B cells (23,24). Other investigators have shown that the levels of IL-6 are elevated in the synovial fluid and serum of RA patients (32). Both in our present study and in a study reported by other investigators (6), RA FLS were found to produce far more IL-6 than did OA FLS (P Ͻ 0.05) ( Figure 6C).…”
Section: Functionality Of Rag-1 and Rag-2 Proteinsmentioning
confidence: 87%
“…Both clinical observations and studies in transgenic mice have shown a link between IL-6 overexpression and several pathologic conditions, including atherosclerosis [53][54][55], Alzheimer's disease [56][57][58][59], and rheumatoid arthritis [60][61][62]. It is worth mentioning that statins, which have become important in the treatment of patients with coronary artery disease [63,64] and also have been reported to have beneficial effects in POAG [65], are associated with a reduction in serum levels of IL-6.…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 synthesis by peripheral blood mononuclear cells can also be induced by TNFa (26) and TGFP (27). Production of IL-6 by the higher proportion of activated mononuclear cells in the rheumatoid joint may partly account for the generally higher levels of IL-6 found in the synovial fluid of patients with rheumatoid arthritis (RA) compared with those with osteoarthritis (22,25,28,29).…”
Section: Discussionmentioning
confidence: 99%